Libertad de expresión y su incidencia en los medios de comunicación del cantón Quevedo, año 2022 - Briones Palacios, Yalile Lisetth (2022)
Freedom of expression is an innate right of human beings, it allows the exposure of ideas, thoughts or opinions, without the need to be punished or excluded for this, and it also makes society more democratic. The objective of this study is to analyze freedom of expression and its impact on the media in the canton of Quevedo. As the project progresses, it is possible to reach the research result, which is that the media take into consideration the freedom of expression of journalists and thus keep updated on issues related to responsible journalism. In the research, once the points of view of citizens and professionals of the journalistic branch are known, it is proposed to carry out appropriate campaigns to the media, aimed at improving relations between the media, with the objective that students and professionals of the career can feel at ease and apply responsible journalism with a high sense of responsibility in favor of the community, the country and the world.